Zeitschrift der Savigny-Stiftung für Rechtsgeschichte: Germanistische Abteilung (De Gruyter, 1861)
The Zeitschrift für Rechtsgeschichte (ZRG, also known as the Savigny Journal) represents an integral part of European legal history research, having made a significant contribution to the current state of the discipline.